Lengilo and Lun Bawang Languages of Sarawak are Sister Languages : Lexicostatistic Study - Hamidah, Abdul Wahab; Nur Ardini Jian, Abdullah; Su Hie, Ting (Asian Scholars Network, 2025)
The Lengilo is one of the minority indigenous groups living in Ba’Kelalan and Lawas, Sarawak. As most people are not aware of the existence of the group, the Lengilo people identify themselves as Lun Bawang. Intermarriages bring the two distinct groups together but it is not known how similar their languages are. The study compares the basic vocabulary of the Lengilo and Lun Bawang languages to determine the level of kinship. The data were collected through interviews with 10 native speakers of Lengilo and Lun Bawang in Ba’Kelalan and Lawas using a list of 100 Swadesh vocabulary items. The 10 informants, consisting of men and women, were aged 56 to 68. The lexicostatistical method was used to identify the percentage of cognate words involves comparing the similarities and differences in the vocabulary of these languages based on Gudschinsky’s (1956) proposed language kinship level table. The results show 94.6% similarity in the form and meaning of Lengilo and Lun Bawang words. The findings suggest that since the divergence between Lengilo and Lun Bawang is minimal, they probably come from the same ancestor language, likely even forming part of a dialect continuum.